2015
DOI: 10.14260/jemds/2015/754
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Epidural Butorphanol and Epidural Morphine for the Relief of Postoperative Pain

Abstract: Epidural administration of various anaelgesics gained increasing popularity following the discovery of opioid receptors in the spinal cord capable of producing potential analgesia. \the analgesic effect seems to be more when epidural anesthesia is continued in the post-operative period as epidural analgesia. It is now clear that epidural administration of opioids relieves patient of extended pain post-operatively. Ours was a comparative study of epidural butorphanal and epidual morphine for the relief of posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Duration of analgesia in the morphine group ranged from 10 to 24 h with a mean ± SD of 16.05 ± 3.14 h. The quality of analgesia was comparable in both groups, and the difference is statistically insignificant ( P > 0.05). [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Duration of analgesia in the morphine group ranged from 10 to 24 h with a mean ± SD of 16.05 ± 3.14 h. The quality of analgesia was comparable in both groups, and the difference is statistically insignificant ( P > 0.05). [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Malik P et al 29 also report that butorphanol provides a longer duration of analgesia, but more sedation compared with fentanyl while increased incidence of nausea and pruritus is associated with the use of the latter. Devulapalli P K, et al 30 recently reported that epidural butorphanol has faster onset of action compared with epidural morphine (14.66 vs 34.76 mins, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with intermittent parenteral application of opioids, epidural administration acts on specific opioid receptors that are abundantly distributed in the posterior horn of the spinal cord, resulting in a more rapid onset of analgesic action and a lower incidence of adverse effects such as nausea, vomiting, and pruritus [28] . Due to its high lipid solubility, bupropion tartrate diffuses in the spinal cord after epidural administration, reducing the transfer of residual drug in the cerebrospinal fluid from the lumbar region to the brainstem, avoiding inhibition of the medullary respiratory centre and reducing the incidence of respiratory depression [29] .…”
Section: Multimodal Analgesic Programme With Bupropion Tartratementioning
confidence: 99%